Embryotoxicity and teratogenic effects of Parmotrema tinctorum (Nyl) Hale on Zebrafish (Danio rerio) and cytotoxic activity of lichen extract on HEK293T cell line - M. Shenbagam, M. Mariraj, R. Kalidoss, S. Jeya Preethi, P. Ponmurugan (International Journal of Modern Agriculture, 2021)
Parmotrema tinctorum (Nyl) Hale an edible lichen, used as a spice and flavouring agent for meat and vegetable preparations by ethnic groups in India and Nepal. In Zebrafish embryos and larva, the therapeutic applications of P.tinctorum widely reported. However the teratogenic effects not reported. This study was aimed to examine the toxicity of P.tinctorum on the promising model for toxicity research, the Zebrafish, because their genetic structure is more similar to human beings. Additionally, we have demonstrated a toxic effect of P.tinctorum extract on the human normal cell line (HEK293T) by MTT assay. The methanol extract of P.tinctorum was extracted by Soxhlet and for embryotoxicity and teratogenicity activities, we use different concentrations (50µg/ml – 200µg/ml) of lichen extracts on twelve selected fertilized Zebrafish embryos. The extract did not exhibit any effect on Zebrafish Survival rate, hatching rate, heartbeat and teratogenicity which was similar to control groups. To conclude that, methanol extract of P.tinctorum is found to have a nontoxic property to zebrafish embryo and human normal cell line (HEK293T) and suggests that this might be safe for consumption.